Hypertensive urgency in nephrogenic diabetes insipidus with concomitant Hinman syndrome. Issue 7 (27th July 2019) - Tan, Yu Guang; Chan, Daniel Wei Keong; Yap, Fabian Kok Peng; Yap, Te-Lu
Abstract : Diabetes insipidus is a syndrome characterised by the inability to conserve water or concentrate urine, leading to excessive excretion of urine. In congenital nephrogenic diabetes insipidus (CNDI), common presentations include failure to thrive, polydipsia, polyuria and dehydration. The long trajectory of the disease, coupled with psycho-behavioural changes as a child grows, can precipitate a period of non-adherence despite initial optimal control, especially in the adolescent age group. Social inconvenience of repeated voiding and nocturnal disturbances can lead to adapted urine holding behaviour, also known as non-neurogenic neurogenic bladder (Hinman syndrome). Anatomical changes in the urinary system, such as bladder trabeculation and hydroureteronephrosis, can subsequently give rise to functional renal impairment. We present a case of CNDI with concomitant Hinman syndrome, resulting in acute renal impairment and hypertensive emergency. We aim to raise awareness of the association between these two entities.